Review paper on Automatic Itinerary Planning for Traveling Services - Pallavi, Bhosale; Sarika, Holkar; Shailaja, Takale; Shweta, Divekar; Rajaram, Ambole (International Journal of Computer Sciences and Engineering, 2015)
The trip planning is very difficult task for peoples, for the places which are not known. So creating an efficient and economic trip plan is the most essential. Although some travel agency can provide some predefined planning of days, which is not suitable for a specific or individual customer. A route search is an enhancement of an ordinary geographic search. Instead of merely returning a set of entities, the result is a route that goes via entities that are relevant to the search [2].For Constructing Travel Itineraries from Tagged Geo Temporal Breadcrumbs develops an end-to-end approach for constructing intra-city travel itineraries automatically by tapping a latent source reacting geo-temporal breadcrumbs left by millions of tourists[3]. A nature-pushed figuring ,imitating the without any preparation creation system for music players, has been beginning late made and named Harmony Search (HS)[4].The extraction of Event and Place Semantics from Flickr Tags that contains, Tags usually manifest in the form of a freely-chosen, short list of keyword associated by a user with a resource such as a photo, web page, or blog entry[5].